ENGLISH STUDENTS' ROUTES FOR LEARNING, FROM LEARNING CONCEPTIONS TO LEARNING OUTCOMES: A Case Study at an Islamic Senior High School of a Pesantren in Bandung - Euis Rina Mulyani, - (2019)
This study was inspired by the concept of learning patterns - consisting of a combination of four learning components: the conceptions, orientations, cognitive, and regulation/metacognitive strategies - reported to have influence on students' learning achievement. The present study was aimed at portraying English students' routes for learning covering their conceptions of learning English, motivations to learn English, and their strategies in learning English. It was also intended to portray high achievers' and low achievers' routes for learning English. The participants were the students of an Islamic Senior High School in Bandung. The data of English learning strategies were gained from 209 students; the conceptions of learning English were from 169 students; and the learning motivations were from 200 students. To answer the questions of this research, both close and open questionnaires were used; the documents of students' records of scores in English subject, their writing product, their answer sheets of the USBN, and the basic competences were studied; and the interview was conducted. The data collected from close questionnaires were analyzed quantitatively by quantifying the frequency and the average of each issue. Meanwhile, the data from open questionnaire, documents, and interview were analyzed qualitatively. Overall, data analysis showed that in terms of learning conceptions, most of the students' conceptions of learning are colored by religious and cultural values - learning English is as a duty. In terms of learning motivations, their motivations were also colored by religious and cultural values - they were mostly motivated by instrumental motivations. In terms of learning strategies, most of them preferred to employ metacognitive strategies. Further, it was found that high achiever students tended to conceive learning variously, both surface and deep learning; be motivated by instrumental motivations; and used more metacognitive and compensation strategies. In contrast, low achievers tended to conceive learning in surface level; more highly triggered by the instrumental motivations; and preferred affective strategies to metacognitive strategies. Finally, this study found that more religious and independent students achieved better learning outcomes regardless of their type of routes for learning.